2020
DOI: 10.1109/ojcoms.2020.2969492
|View full text |Cite
|
Sign up to set email alerts
|

Ergodic Sum Rate Analysis of UAV-Based Relay Networks With Mixed RF-FSO Channels

Abstract: Unmanned aerial vehicle (UAV)-based communications is a promising new technology that can add a wide range of new capabilities to the current network infrastructure. Given the flexibility, costefficiency, and convenient use of UAVs, they can be deployed as temporary base stations (BSs) for ondemand situations like BS overloading or natural disasters. In this work, a UAV-based communication system with radio frequency (RF) access links to the mobile users (MUs) and a free-space optical (FSO) backhaul link to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 40 publications
0
53
0
Order By: Relevance
“…Effective iterative lowcomplexity algorithms have been proposed to solve the optimization problems associated with these types of relay networks [93]. Work by Ajam et al [94] established the ergodic sum rate of a UAV-based relay networks with mixed RF and free-space optical channels. Their analysis showed that these networks are able to provide high rate, which can be further enhanced by the optimal positioning of the UAV.…”
Section: Urllc-enabled Uav Communication Systemmentioning
confidence: 99%
“…Effective iterative lowcomplexity algorithms have been proposed to solve the optimization problems associated with these types of relay networks [93]. Work by Ajam et al [94] established the ergodic sum rate of a UAV-based relay networks with mixed RF and free-space optical channels. Their analysis showed that these networks are able to provide high rate, which can be further enhanced by the optimal positioning of the UAV.…”
Section: Urllc-enabled Uav Communication Systemmentioning
confidence: 99%
“…This section presents a study of two UAV selection schemes (HM and BDS) that guarantee a certain quality-of-service (QoS). In extreme physical conditions and high terrain areas UAVs can be used as moving relay nodes to relay the information from one location to another location [28]- [31]. In such scenarios, the efficient UAV selection and the position optimization of UAVs are of utmost importance in order to attain a good performance for the data transmission.…”
Section: Uav Selectionmentioning
confidence: 99%
“…The advantage of using BA UAV‐based relay has been discussed in [118]. In [118], the communication system considered is a DF UAV‐relay connecting MUs via RF links to a ground station (GS) via an FSO back‐haul link. Due to the mutual orthogonality of the links, the UAV‐based relay can simultaneously transmit and receive.…”
Section: Unmanned Aerial Vehicles In Relaying Networkmentioning
confidence: 99%
“…The RF and FSO channels depend on the UAV's location and instability, respectively, where the relative position of the UAV with respect to the MUs affects the LOS connection in the RF link, whereas the instability of the UAV affects the FSO channel's quality. Ajam et al [118] analyse the E2E system performance of networks employing UAVs as BA and non‐BA relays, in terms of ergodic sum rate. Results show that, when the weather conditions worsen and the atmospheric loss in the FSO channel intensifies, positioning the UAV closer to the GS improves the back‐haul channel's quality.…”
Section: Unmanned Aerial Vehicles In Relaying Networkmentioning
confidence: 99%
See 1 more Smart Citation